Theoretical and Methodological Basis of Studying the Development of National Tourism (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, information on the development of world and national tourism, the role of tourism in the economy, the characteristics of the development of outbound tourism by region, regions with developed inbound tourism, countries with developed tourism, trends in the modern tourism market and other aspects are highlighted.